An Analysis on Students’ Speaking Ability of Procedure Text at Senior High School - Karina Kurnia Marbes; Andi Idayani (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2022)
This research discusses the students’ speaking ability of Procedure Text at the Second Grade Students of SMA Tri Bhakti Pekanbaru. The objective of the research is to know the students’ speaking ability in procedure text and to find out which aspectt is the most dominant problem for the students in speaking. The design of this research was qualitative research. The result of data was students’ comprehension score was 3.15 because most of them understood the directions on the speaking test well and they also conveyed the procedure text sequentially using the simple present tense correctly so that the listener could understand them although there were several problems. Students’ fluency score was 3.15 because most of the students’ present the procedure text fluently and smoothly even though some students stammered and paused several times. Students’ grammar score was 3.13 because most of them were good at arranging their sentences correctly according to the grammar rules using the simple present tense even though they made some mistakes. The students' pronunciation score was 2.86 because some students had difficulty in pronouncing some words and there were some confusions with the listener, although not all students did so. Students’ vocabulary score was 2.92 because some students had problem with vocabulary mastery and use inappropriate vocabulary, but overall the students have sufficient vocabulary to express tips simply related to the topic. In conclusion, the students' speaking ability on procedure text is in a good category.